Developing Assessment Instrument of Data, Technology, and Human Literacy in Physics Learning - Dewi, Candra; Rusilowati, Ani; Fianti, Fianti (Universitas Negeri Semarang, 2019)
This study aims to determine validity of the assessment instrument data, technology, and human literacy in physics learning. The research method uses research and development (RnD) with modified 4-D model until development stage. Instrument of validation was assessed by 6 validators. The instrument was tested by 36 students of class X SMK Texmaco Semarang. The form of instruments is multiple choice test with 21 item to measure the cognitive domain. Data analysis in this research are tests of content validity, reliability, internal consistency, discrimination power, and level of difficulty. The results of the content validity by using Aiken’s coefficient get an average score 0.84 with a valid category at significance level of 0.05. Cronbach’s Alpha and ICC values from reliability test are 0.77 and 0.806 with reliable categories. The results of internal consistency showed that 80.95% items had a good internal consistency. There are 4 items with category not used from the discrimination power test. Furthermore from the results of the difficulty level, 7 items are easy, 13 items are medium, and 1 item is difficult. Based on results of the instrument analysis can be concluded that the instrument developed were valid and reliabel then can be used to measure ability of data, technology, and humans literacy in physics learning.